Pengaruh Social Support terhadap Loneliness pada Mahasiswa Rantau di Kota Bandung - Kezkia Meianisa; Sita Rositawati (Bandung Conference Series: Psychology Science, 2023)
Abstract. The results of research on social support show that social support has many benefits in overcoming various problems. One of the benefits of social support is to help overcome loneliness, where loneliness according to Russell (1996) is "a social relationship that does not match what is desired, including feelings of anxiety, distress, and the perception of a lack of social relationships in a person". This research is a quantitative research that aims to see the influence of social support on loneliness. The respondents totaled 157 first-year students who come from outside the island of Java in the city of Bandung. Samples were selected by accidental sampling technique. Loneliness was measured using a loneliness scale version 3 (UCLAversion 3) measuring instrument. Social Support is measured by a questionnaire that refers to aspects of Sarafino theory (2011). The social support scale has the reliability value of the coefficient alpha (a) = 0.938 and the loneliness scale has the reliability value of the coefficient alpha (a) = 0.822. Based on the, it was found that there was a negative influence of social support on loneliness in students who come from outside the island of Java. The effective contribution given by the social support variable to loneliness in students who come from outside the island of Java was 2.5% and the remaining 97.5% was influenced by other factors that were not studied in this study. Abstrak. Hasil- hasil penelitian mengenai social support menujukkan bahwa social support memiliki banyak manfaat dalam mengatasi berbagai permasalahan. Salah satu manfaat dari social support yaitu untuk membantu mengatasi loneliness, dimana loneliness menurut Russell (1996) merupakan “hubungan sosial yang tidak, sesuai dari apa yang diinginkan, termasuk perasaan gelisah, tertekan, dan persepsi kurangnya hubungan sosial pada diri seseorang”. Penelitian ini merupakan penelitian kuantitatif yang bertujuan untuk melihat pengaruh social support terhadap loneliness. Responden berjumlah 157 mahasiswa rantau tahun pertama di Kota Bandung. Sampel dipilih dengan Teknik Accidental Sampling. Loneliness diukur menggunakan alat ukur loneliness scale version 3 (UCLAversion 3). Social Support diukur dengan kuesioner yang mengacu pada aspek teori Sarafino (2011). Skala social support memiliki nilai reliabilitas koefisien alpha (a) = 0.938 dan skala loneliness memiliki nilai reliabilitas koefisien alpha (a) = 0.822. Berdasarkan hasil penelitian ditemukan bahwa ada pengaruh negatif dari social support terhadap loneliness pada mahasiswa rantau. Artinya semakin tinggi social support yang diperoleh mahasiswa rantau, maka loneliness akan semakin rendah dan begitu juga sebaliknya. Sumbangan efektif yang diberikan variabel social support terhadap loneliness pada mahasiswa rantau adalah sebesar 2,5% dan sisanya yaitu 97,5% dipengaruhi oleh faktor-faktor lain yang tidak diteliti dalam penelitian ini.